2009
DOI: 10.1103/physrevb.80.033303
|View full text |Cite
|
Sign up to set email alerts
|

Giant Rabi splitting between localized mixed plasmon-exciton states in a two-dimensional array of nanosize metallic disks in an organic semiconductor

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 19 publications
6
110
1
1
Order By: Relevance
“…When the incidence angle is in the range of 25°-31°, as marked by the black dashed lines in Fig. 3a, a Rabi splitting-type anticrossing 35,36 between D1 and D3 is observed on both the simulated and measured reflectance spectra (see Supplementary Fig. S1 for the mode exchange details).…”
Section: Pmmamentioning
confidence: 98%
“…When the incidence angle is in the range of 25°-31°, as marked by the black dashed lines in Fig. 3a, a Rabi splitting-type anticrossing 35,36 between D1 and D3 is observed on both the simulated and measured reflectance spectra (see Supplementary Fig. S1 for the mode exchange details).…”
Section: Pmmamentioning
confidence: 98%
“…A number of studies have demonstrated plasmon-exciton in the strong coupling limit between an organic exciton semiconductor and a surface plasmons [11,12] and localized surface plasmons geometries [13][14][15][16][17]. Studies have demonstrated that colloidal Au nanoshell-J-aggregate particles exhibit strong coupling between the localized plasmons of a nanoshell and the excitons of molecular J-aggregates adsorbed on its surface [13].…”
Section: Papermentioning
confidence: 99%
“…Studies have demonstrated that colloidal Au nanoshell-J-aggregate particles exhibit strong coupling between the localized plasmons of a nanoshell and the excitons of molecular J-aggregates adsorbed on its surface [13]. The interaction of an organic exciton in a J-aggregate and surface plasmon polariton modes of nanostructured hole arrays or of nanosize metallic disks with different array periods was reported to exhibit strong coupling [14][15][16]. Tuning of plasmon-exciton coupling strength has been reported for strongly coupled exciton-plasmon states in Au nanodisk arrays coated with J-aggregate molecules achieved by changing the incident angle of incoming light, rather than changing the geometry 2 of the plasmonic nanomaterial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4]. More recently, it was demonstrated between SPs and excitons in organic semiconductors [5,6,7]. It is a phenomenon that is interesting both from the point of view of fundamental quantum physics as well as from the point of view of technology.…”
Section: Introductionmentioning
confidence: 99%